2018
DOI: 10.1063/1.5045356
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antigen size, binding site valency, and flexibility on fab-antigen binding near solid surfaces

Abstract: Next generation antibody microarray devices have the potential to outperform current molecular detection methods and realize new applications in medicine, scientific research, and national defense. However, antibody microarrays, or arrays of antibody fragments (“fabs”), continue to evade mainstream use in part due to persistent reliability problems despite improvements to substrate design and protein immobilization strategies. Other factors could be disrupting microarray performance, including effects resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…These results suggested that avidity, which measures the total strength of binding between an antibody and its antigen, was the leading force involved in the binding of multimeric analytes. These results agreed with the observation of Bush and Knotts [ 22 ]; indeed, the authors, thanks to the developed coarse-grain model, found that multiple binding sites stabilize the immunocomplexes in microarrays.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggested that avidity, which measures the total strength of binding between an antibody and its antigen, was the leading force involved in the binding of multimeric analytes. These results agreed with the observation of Bush and Knotts [ 22 ]; indeed, the authors, thanks to the developed coarse-grain model, found that multiple binding sites stabilize the immunocomplexes in microarrays.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent work in this regard, the Knotts group tried to devise a reliable heuristics to identify optimal attachment locations in typical proteins ( Smith et al, 2021 ), a protocol which may be promising when applied to enzyme immobilization. Using coarse-grained MD simulations they initially predicted how external factors-like confinement, tethering configuration, surface hydrophobicity and binding site valency-may affect protein stability and folding pathways ( Rathore et al, 2006 ; Bush et al, 2015 ; Bush et al, 2017 ; Bush et al, 2018 ). Additionally, they performed tethering and PEGylation at a limited number of sites in the loop regions of lysozyme to prove the capability of predicting well-performing functionalization sites ( Wei et al, 2010 ; Wei et al, 2011 ; Wei et al, 2013 ).…”
Section: Computational Protocols For Predicting Immobilization Sitesmentioning
confidence: 99%
“…The multiple binding leads to the stabilization of the Ab-Ag complexes, suggesting that avidity is the leading force involved in the binding of multimeric Ags. This occurs in both oriented and non-oriented ELISAs [59,60]. A clue to the role of affinity and avidity on the analytical sensitivity of ELISAs was obtained by comparing a non-oriented and an oriented ELISA for ferritin, a multimeric protein.…”
Section: Effects Of Antibody and Antigen Properties On The Sensitivit...mentioning
confidence: 99%